2001
DOI: 10.1007/s004420100689
|View full text |Cite
|
Sign up to set email alerts
|

Competition and habitat use in native Australian Rattus: is competition intense, or important?

Abstract: This study investigates patterns of habitat use and competition in sympatric populations of the bush rat, Rattus fuscipes, and swamp rat, R. lutreolus, in the Blue Mountains National Park, New South Wales, Australia. Radiotracking showed that the home ranges of R. fuscipes tended to occupy woodland more than those of R. lutreolus, whereas use of heath and sedgeland by both species was equal. Home range overlaps were less between the two species than between individuals of R. lutreolus. Trap-captures showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 73 publications
1
44
0
Order By: Relevance
“…In other salmonids, such as brown trout and Atlantic salmon (Salmo salar L.), habitat use by juvenile salmon appears restricted through interactive segregation, brown trout being more aggressive and a better defender of deep pool areas in rivers than salmon (Heggenes et al 1999), whereas juvenile coho salmon (Oncorhynchus kisutch) defend deep, low-velocity pools and displace steelhead trout (Oncorhynchus mykiss) into shallow, high-velocity riZes (Young 2004). Likewise, interference competition gives the Australia swamp rat (Rattus lutreolus) priority over the bush rat (Rattus fuscipes) to the preferred moist habitats containing important food and shelter resources (Maitz and Dickman 2001).…”
Section: Discussionmentioning
confidence: 97%
“…In other salmonids, such as brown trout and Atlantic salmon (Salmo salar L.), habitat use by juvenile salmon appears restricted through interactive segregation, brown trout being more aggressive and a better defender of deep pool areas in rivers than salmon (Heggenes et al 1999), whereas juvenile coho salmon (Oncorhynchus kisutch) defend deep, low-velocity pools and displace steelhead trout (Oncorhynchus mykiss) into shallow, high-velocity riZes (Young 2004). Likewise, interference competition gives the Australia swamp rat (Rattus lutreolus) priority over the bush rat (Rattus fuscipes) to the preferred moist habitats containing important food and shelter resources (Maitz and Dickman 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Maitz and Dickman (2001) found that intense competition between R. lutreolus and R. fuscipes resulted in R. fusicpes partial exclusion from the better microhabitats. It is possible in the present study that R. lutreolus restricted R. fuscipes access to resources in the corridor.…”
Section: Discussionmentioning
confidence: 98%
“…Mark and recapture studies as well as radio-telemetry indicate home range distances are usually less than 200 m in length (Warneke 1971;Wood 1971;Robinson 1987), or 0.8-1.2 ha in area (Maitz and Dickman 2001), and are known to vary between sexes (Wood 1971), seasons (Robinson 1987), and density of individuals (Woodside 1983). Males generally occupy larger home ranges than females, and may increase home range movements during the breeding season.…”
Section: The Study Species-rattus Fuscipes Subspecies Assimilismentioning
confidence: 99%